Groundwater irrigation planning under multiple objectives : Sukhothai Project zone 1, Thailand - Mainuddin, Md.; Gupta, Ashim Das; Onta, Pushpa Raj; Loof, Rainer; Kono, Yasuyuki; The Royal Government of The Netherlands (Bangkok : Asian Institute of Technology, 1994)
Water is one of the main limiting resource that influence on the crop area planning and management decision in all irrigation project. In water resources systems the availability of water supplies from the natural resources varies randomly in amount and is often not adequate to meet the demand. Selection of a suitable crop plan to get the maximum social and economic benefit under this limiting condition is a formidable task for engineers and planners. This study deals with one such problem of a groundwater irrigation project in Thailand. A monthwise crop area planning model is formulated for determining the optimal cropping pattern and the groundwater abstraction requirement. Two objectives, maximization of net economic benefit and maximization of irrigated area, those are often aspired to be improved by both the irrigation authority and the individual farmers are considered in model formulation. To match with uncertainty of resources availability, the model is solved for three levels of reliability of resources (80%, 50% and 20%). Moreover, the operational reliability of the tubewells are determined and the comparison of supply and demand for the past ten years are carried out. The effect of certain level of deficit irrigation on the net benefit and cropping intensity as well as on the yield of crops are also assessed by considering three levels (no deficit, 25% deficit and 50% deficit) of water application to the crops. Optimal cropping patterns are obtained for different alternative scenarios at all levels of reliability for maximization of net benefit and irrigated area. The result of crop planning model indicates that there is a conflict exists between the two objectives. To minimize that conflict and to select the best alternative multiobjective analysis is carried out by Analytic Hierarchy Process and Compromise programming considering the preference of the decision makers. It is found that the net benefit obtained from the project can be increased by 50% from the existing benefit and cropping intensity can be increased to 150% from the existing 94%, even considering the lower availability of resources by providing full irrigation to the crops. Recommendations is made for the best alternative.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Civil Engineering
Thesis (M. Eng.) - Asian Institute of Technology, 1994
Keywords: Water, Underground -- Thailand -- Sukhothai